2022
DOI: 10.1093/europace/euac090
|View full text |Cite
|
Sign up to set email alerts
|

The G213D variant in Nav1.5 alters sodium current and causes an arrhythmogenic phenotype resulting in a multifocal ectopic Purkinje-related premature contraction phenotype in human-induced pluripotent stem cell-derived cardiomyocytes

Abstract: Aims Variants in SCN5A encoding Nav1.5 are associated with cardiac arrhythmias. We aimed to determine the mechanism by which c.638G>A in SCNA5 resulting in p.Gly213Asp (G213D) in Nav1.5 altered Na+ channel function and how flecainide corrected the defect in a family with multifocal ectopic Purkinje-related premature contractions (MEPPC)-like syndrome. Methods and results Five patients carrying the G213D variant were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…15,34 One variant, G213D which substitutes a bulky aspartate for a small glycine in the Na V 1.5 domain 1 S3-S4 linker, has been reported to generate both a large window current and a gating pore current at negative potentials. 13 G213D iPSC-CMs displayed afterdepolarizations that were corrected with flecainide; whether G213D interacts with the GCTC was not addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,34 One variant, G213D which substitutes a bulky aspartate for a small glycine in the Na V 1.5 domain 1 S3-S4 linker, has been reported to generate both a large window current and a gating pore current at negative potentials. 13 G213D iPSC-CMs displayed afterdepolarizations that were corrected with flecainide; whether G213D interacts with the GCTC was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations are thought to generate a second (non-physiologic) ion permeation pathway in the S1-S4 gating region, leading to a “gating pore” current or omega current. 6,9,10 Several additional variants that are not in S4 arginines have been described in MEPPC (A204E, 11 L828F, 12 G213D, 13 and M1851V 14 ) and these variants are mainly thought to act through alternate mechanisms such as shifts in the voltage-dependence of channel activation and/or inactivation generating an increased “window current”.…”
Section: Introductionmentioning
confidence: 99%
“… 126 The G213D variant in Nav1.5 in the SCN5A gene is associated with a severe form of arrhythmic DCM that may be cure by antiarrhythmic drugs. 127 The role of common variants has also been reported thanks to GWAS analysis that have identified new DCM-associated SNPs. 128 Polygenic risk scores have recently been shown to have predictive value for DCM prognostic.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…In a recent study, Calloe et al demonstrated that flecainide treatment reduced the window current in hiPSC-CMs with the SCN5A -G231D mutation, and had beneficial effects in patients carrying this mutation. 117 Despite the well-established link with Na + channels, SCN5A mutations are found in only 20% of BrS patients, and their presence is not necessarily always causally related since SCN5A genetic variants are frequently observed in the general population, some of which do not affect Na + channel function. 118 Overall, BrS is characterized by extensive variability in disease severity as well as reduced penetrance, and a polygenic basis is now increasingly recognized.…”
Section: Inherited Arrhythmia Syndromes and Arrhythmogenic Cardiomyop...mentioning
confidence: 99%